(untitled) (INNOVATIVE ECONOMY, 2025)
Sydorovych O.Yu. THE POTENTIAL FOR THE DEVELOPMENT OF RESEARCH ECOSYSTEMS IN UKRAINE Purpose. The aim of the article is to is to conceptually substantiate the theoretical and methodological foundations for the functioning of research ecosystems and to provide a comprehensive analysis of their development potential on a national and global scale. This analysis is based on international determinants, including the Global Innovation Index, the international university ranking (QS World University Rankings), and the Global Startup Ecosystem Development Index. Methodology of research. The following general scientific and special methods were employed in the research process: induction and deduction ‒ used at the stage of collecting, systematizing, and processing information on global and national trends in scientific and technical policy to identify cause-and-effect relationships between external challenges (particularly military risks and competition for resources) and the necessity for the ecosystem transformation of Ukraine’s scientific sphere; аnalysis and synthesis ‒ applied to assess the essence and structural elements of research ecosystems, determine their potential for ensuring systemic sustainability and accelerated commercialization of scientific results, and for developing strategic principles for their future growth; abstract and logical method ‒ utilized to generalize theoretical concepts and form a comprehensive understanding of the research ecosystem as an adaptive network model capable of responding effectively to crisis conditions and global challenges.; comparative cethod ‒ employed to compare models of research ecosystem functioning in countries with a high level of innovative development and to identify the most effective approaches for implementation in Ukraine; graphical method ‒ used to visualize the study’s results, specifically for structuring the properties and functions of the ecosystem and determining the dynamics of key trackers of Ukraine’s innovative development. Findings. Key indicators that determine the potential of research ecosystems were systematized, focusing on institutional quality (based on QS World University Rankings) and innovative activity (based on the Global Startup Ecosystem Report). An analysis of Ukraine’s positions in global rankings revealed the weak standing of Ukrainian universities against the backdrop of the high resilience of the national startup ecosystem (42nd place globally, showing a 26% growth). It was established that the dominant global trends are the rapid development of Artificial Intelligence (AI) and the increased sensitivity of ecosystems to geopolitical changes, which necessitates a strategic focus on regional orientation and management planning. The study found that Ukraine’s innovation potential demonstrates high resilience, confirmed by the rapid development of key cities, but requires strengthening through the transformation of universities into central innovation hubs and the acceleration of research commercialization. Prospects for further development were identified, emphasizing the necessity of public-private partnerships and robust international support for targeted scaling in critical technology sectors, such as SaaS and AI. Originality. It is proven that the development of research ecosystems in Ukraine, in contrast to the traditional institutional-oriented model of science, is taking place through strengthening the role of universities and their transformation from educational institutions into key innovation hubs and integration centers. This transformation makes it possible to enhance the economic self-sufficiency of the research sector and the effectiveness of its contribution to the country’s recovery. The provisions concerning the growing role of the commercialization of scientific research as a factor in the resilience of the national research system have been further developed. Approaches to substantiating strategic priorities for the development of research ecosystems in the face of modern challenges and threats have been improved. Practical value. The results of the study can be used in the formation and adjustment of state scientific, technical and innovation policy, as well as strategic plans for the development of universities and scientific institutions. Based on the findings of the study, the feasibility of strengthening institutional mechanisms for the commercialization of research outcomes through the development of technology transfer offices and targeted support for research and innovation projects focused on post-war recovery and national security needs is substantiated. The study also proposes improving models of public–private partnership in applied research and technological development, as well as integrating universities and research institutions into international innovation networks in order to ensure technological sovereignty and enhance the resilience of the national research system under conditions of global competition and military challenges. Key words: ecosystem, research ecosystem, innovative business startups, innovation, development potential.